The Effect of Book Value, Debt to Equity Ratio, Roa, Interest Rate and Exchange Rate at Jakarta Islamic Index (JII) - Rahayu, Heffi Christya; Lestari, Etty Puji; Kuniawati, Tri R. (LPPM Universitas Terbuka, 2021)
The Jakarta Islamic Index (JII) consists of 30 companies whose liquid assets have large capitalization compared to other companies. JII then becomes a measure of performance in choosing a halal stock portfolio. This study aims to determine the factors that affect the company's stock price in JII. This research uses quantitative methods with the study applied is panel data regression analysis method. The data used in this study is secondary data obtained from Bank Indonesia, the Financial Services Authority, the Indonesia Stock Exchange, and other literature. Secondary data or qualitative data used is panel data from 30 companies in JII. Findings. This research shows that Book Value, Debt Equity Ratio, Return on Assets (ROA), Interest Rate, and Exchange Rate simultaneously significantly affect the Stock Price. JII consists of 30 companies whose liquid assets have large capitalizations compared to other companies. Market capitalization is an indicator of stock development, if there is a decline in stock prices, the market capitalization will decrease.